Mechanical Testing of a Synthetic Canine Gastrocnemius Tendon Implant. Issue 5 (July 2015) - Morton, Mark A.; Whitelock, Richard G.; Innes, John F.
<x xml:space="preserve">Abstract</x> Objective To test a polyethylene terephthalate prosthesis (STIF, Chenove, France) for gastrocnemius tendon repair in dogs (cadaver model). Study Design In vitro mechanical study. Animals Pelvic limbs (n = 8) from 4 recently euthanatized adult dogs (weighing 30–45 kg). Methods Proximally the implant was sutured at the myotendinous junction of the gastrocnemius and distally secured in a 4.5 mm blind ending tunnel in the medullary cavity of the calcaneus using an interference screw (STIF, Chenove, France). Proximal and distal fixation were tested independently using an electrodynamic testing machine (Electropuls 3000, Instron, UK). Results Mean ± SD failure loads for the proximal fixation (266.13 ± 43.88 N) was significantly less than for the distal fixation (649.25 ± 210.36 N; P = .042, paired t‐test). Mean stiffness of the proximal and distal constructs were 19.08 ± 8.16 N/mm and 139.76 ± 24.51 N/mm, respectively. Conclusions Failure loads exceeded the values reported after experimental repair of chronic gastrocnemius tendon injuries using other methods involving suturing tendon to bone. Failure of this repair method clinically is predicted to occur proximally at the level of the myotendinous junction.